Solar technology : the Earthscan expert guide to using solar energy for heating, cooling, and electricity - Thorpe, Dave, 1954-; Earthscan (Abingdon, Oxon ; New York : Earthscan, 2011)
Solar energy is free, abundant and sustainable, with many methods existing to harness it. This guide is the essential introduction to the subject, explaining how the technologies work, how best they should be employed, and the costs and benefits of using them
Solar energy is free, abundant and sustainable, with many methods existing to harness it. This guide is the essential introduction to the subject, explaining how the technologies work, how best they should be employed, and the costs and benefits of using them
-- Passive solar building -- Solar water heating -- Solar space heating -- Further solar thermal power applications -- Photovoltaics -- Stand-alone photovoltaics -- Concentrating solar power
Includes bibliographical references and index
Keywords: Solar energy; Solar buildings